Cover Feature: High‐Shear‐Imparted Tunable Fluorescence in Polyethylenimines (ChemPhotoChem 4/2018). Issue 4 (30th March 2018) - Luo, Xuan; Al‐Antaki, Ahmed Hussein Mohammed; Pye, Scott; Meech, Robyn; Zhang, Wei; Raston, Colin L.
Abstract : The Cover Feature highlights the fabrication of polyethylenimine‐based nanoparticles with tunable fluorescence, formed in the absence of auxiliary materials, under high shear in an angled vortex fluidic device. More information can be found in the Communication by X. Luo et al. onpage 343 in Issue 4, 2018 (DOI:10.1002/cptc.201700206 ).